Transaction Costs and Digital Transformation: pathways to operational efficiency (Revista Brasileira de Contabilidade e Gestão, 2024)
Objective(s): Digital Transformation (DT) has triggered profound changes in various sectors of society, affecting not only the way organizations operate, but also how they conduct and perceive economic transactions. Thus, using the Transaction Cost Theory (TCT) developed by Williamson (1985) from the concepts of Coase's (1937) seminal proposal, this study sought to identify the interference of efficiency motivated by Digital Transformation in the Theory.
Keywords: digital transformation; operational efficiency; transaction cost theory; systematic review